Cross-regulation between SOX9 and the canonical Wnt signalling pathway in stem cells - Wang, Jiajia; Wan, Xichen; Le, Qihua (Frontiers in Molecular Biosciences, 2023)
SOX9, a member of the SRY-related HMG-box transcription factors, has been reported to critically regulate fetal development and stem cell homeostasis. Wnt signalling is a highly conserved signalling pathway that controls stem cell fate decision and stemness maintenance throughout embryonic development and adult life. Many studies have shown that the interactions between SOX9 and the canonical Wnt signalling pathway are involved in many of the physiological and pathological processes of stem cells, including organ development, the proliferation, differentiation and stemness maintenance of stem cells, and tumorigenesis. In this review, we summarize the already-known molecular mechanism of cross-interactions between SOX9 and the canonical Wnt signalling pathway, outline its regulatory effects on the maintenance of homeostasis in different types of stem cells, and explore its potential in translational stem cell therapy.